Vom maroden Hafen zur glitzernden Nebencity: die London Docklands: Eine Bilanz nach drei Jahrzehnten Strukturwandel - Zehner, Klaus (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The transformation of former docks close to city centers into profitable locations for first-class offices and top-quality residences does belong to the most striking changes in contemporary port cities. In this regard London Docklands act as a prime example in Europe. However the development from scruffy docks into a postmodern edge city which has taken place under prime minister Thatcher during the 1980ies and early 1990ies was discussed quite emotionally and controversially at that time. The goal of this paper is to analyse both the urban, economic and social ramifications and the chosen strategies of the docks regeneration exempt from ideological and political discussions.